Intrauterine pneumonia in premature newborns: pre-rising factors and peculiarities of clinical manifestations - A. D. Bogomazov; I. G. Khmelevskaya; T. A. Emelyanova; E. V. Matvienko; L. Yu. Zaitseva (Лечащий Врач, 2021)
The aim of the study was to find a connection between various pathological conditions observed in pregnant women with the development of intrauterine pneumonia (IUP) in their newborn children, in this research, another poor of interest was study the clinical course of this pathology in children with different premorbid backgrounds. The study was conducted on the basis of the Regional budgetary health institution «Kursk regional children's hospital No. 2» of the health Committee of the Kursk region. The materials of the study were extracts of newborns from the maternity hospital, medical records of the inpatient neonatal Department (medical documentation form No. 003/y) and personal data of mothers. Statistical processing was carried out with the help of the company's package StatSoft Statistica 8.0 for Windows. Our study showed that the burdened history of mothers plays a significant role in the development of intrauterine pneumonia and was observed in 85.0% of these women. It was found that the presence of IgG in mothers to various infectious agents leads to a significant increase in the incidence of IUP in newborns (p < 0.05). The features of the clinical picture of pneumonia in fullterm newborns were revealed. Revealed the frequent combination of IUP with perinatal hypoxic-ischemic lesion of the Central nervous system. It is established that the clinic is manifested mainly by respiratory disorders and to a lesser extent intoxication syndrome. The diagnostic significance of determining the level of C-reactive protein was established. High efficiency of cephalosporin antibiotics against pathogens of this pathology in newborns is proved. The data obtained in the course of the study are applicable in practice to identify the risk group of mothers, children who are prone to the occurrence of intrauterine pneumonia, optimization and alertness in the diagnosis and appointment of timely antibacterial therapy on the basis of empirical data.